Modulators of the Vascular Endothelin Receptor in Blood Pressure Regulation and Hypertension - Khalil, Raouf A. (2011)
Endothelin (ET) is one of the most investigated molecules in vascular biology. Since its discovery two decades ago, several ET isoforms, receptors, signaling pathways, agonists and antagonists have been identified. ET functions as a potent endothelium-derived vasoconstrictor, but could also play a role in vascular relaxation. In endothelial cells, preproET and big ET are cleaved by ET converting enzymes into ET-1, −2, −3 and −4. These ET isoforms bind with different affinities to ET(A) and ET(B) receptors in vascular smooth muscle (VSM), and in turn increase [Ca(2+)](i), protein kinase C and mitogen-activated protein kinase and other signaling pathways of VSM contraction and cell proliferation. ET also binds to endothelial ET(B) receptors and stimulates the release of nitric oxide, prostacyclin and endothelium-derived hyperpolarizing factor. ET, via endothelial ET(B) receptor, could also promote ET re-uptake and clearance. While the effects of ET on vascular reactivity and growth have been thoroughly examined, its role in the regulation of blood pressure and the pathogenesis of hypertension is not clearly established. Elevated plasma and vascular tissue levels of ET have been identified in salt-sensitive hypertension and in moderate to severe hypertension, and ET receptor antagonists have been shown to reduce blood pressure to variable extents in these forms of hypertension. The development of new pharmacological and genetic tools could lead to more effective and specific modulators of the vascular ET system for treatment of hypertension and related cardiovascular disease.